Therapeutic Benefits of Lenalidomide in Hematological Malignancies - Mohammed Shafi Abdulsalam; Durai Mavalavan Vasudevan Manimoliyan (Indian Journal of Medical Specialities)
Lenalidomide is an immunomodulatory agent, which has action against most of the hematological malignancies. Apart from its immunomodulation, it has other properties such as antiproliferation and antiangiogenesis. It is not only effective in myelodysplastic syndromes and myeloma, recent studies show its effective action on newly diagnosed and relapsed/refractory lymphomas as well. Addition of lenalidomide to standard therapy is associated with lesser central nervous system relapse in diffuse large B-cell lymphomas. Lenalidomide shows promising results in Hodgkin's lymphomas and leukemias (acute myeloid leukemia and chronic lymphocytic leukemia). Dose escalation may be an option in nonresponders with caution in side effects.